Influence of teachers‘ instructional practice and supervision on students‘ approaches to learning - Quainoo, Frank (University of Cape Coast, 2024)
Today, an integrated use of teacher-centred and student-centred instructional practice has emerged. But there is no clarity on which of these three instructional practice Economics teachers use for their instructions. Instructional supervision is infrequent and below standard practice. Based on this, the study examines the influence of teacher instructional practice and supervision on students‘ approaches to learning. Using a mixed-methods approach, data from 346 students and 33 teachers selected through proportionate sampling and criterion sampling respectively revealed that teachers often combined various instructional practices rather than exclusively using teacher-centered or student-centered instructional practices. Strategic Deep and Surface learning were the two learning approaches that students exhibited the most. The infrequent nature of instructional supervision and the problems it faces were both discovered. Digitalization of supervision, supervisor incentive, and institutionalizing external supervision were all suggested. This study's findings recommend corporate professional development workshops and trainings be organized for both teachers and students on integrated instructional practice and approaches to learning respectively.
xiii, 320p;, ill
Keywords: Economics; Surface learning; Digitalization; external supervision